Tube for semiconductor manufacturing apparatus
By optimizing the monomer composition and processing conditions of fluoropolymer, the problems of insufficient bondability and gas shielding of pipes for semiconductor manufacturing devices are solved, and excellent bondability and gas sealing effect are provided, which is suitable for liquid and gas transportation of semiconductor manufacturing devices.
Patent Information
- Application Number
- CN202380088590.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-12-27
- Publication Date
- 2025-08-01
AI Technical Summary
The existing tubes for semiconductor manufacturing devices are prone to leakage when the joint is bonded and the gas shielding is insufficient, making it difficult to meet the needs of efficient bonding and gas closure.
The fluoropolymer with a specific composition is used to meet the requirements of permanent creep strain of more than 4.5%, creep speed of less than 2.60%, bending elastic modulus of less than 1100MPa and crystallinity of more than 42.0%. The pipe performance is optimized by adjusting the monomer composition and processing conditions.
Excellent bonding and gas shielding with the joint are achieved, ensuring that leakage is not easy after bonding, and is suitable for liquid and gas transportation of semiconductor manufacturing devices.
Smart Images

Figure BDA0005462728970000211
Abstract
Description
Technical Field
[0001] The present invention relates to a tube for a semiconductor manufacturing apparatus. Background Art
[0002] Fluorine-containing polymers are used in various fields as molding materials because of their excellent heat resistance, chemical resistance, mechanical properties, electrical properties, surface properties, etc. The molding materials constitute pipes for conveying various fluids used in manufacturing apparatuses for semiconductor and other electronic devices, chemicals, and pharmaceuticals, joint members (connecting members) for pipes, storage containers, pumps, and filter housing members. For example, Patent Document 1 discloses a PFA molded body which is a molded body made of a copolymer (PFA) of tetrafluoroethylene (TFE) and perfluoro(alkyl vinyl ether) (PAVE), the PAVE content of the copolymer being 1 to 10 mol%, and having specified values for its flexural life value, zero-shear viscosity, and thermal weight loss. Prior Art Documents Patent Documents
[0003] Patent Document 1: International Publication No. 2019 / 003265 Summary of the Invention Technical Problem to be Solved by the Invention
[0004] When a fluorine-containing polymer is used as a constituent material of a tube for a semiconductor manufacturing apparatus, in addition to properties such as chemical resistance, mechanical strength, and electrical insulation, it is required to have excellent properties (hereinafter also collectively referred to as "joinability with a joint") such that when a joint in a semiconductor manufacturing apparatus is joined to the above tube to form a joint portion, the joining can be easily performed, and when liquids and gases pass through the hollow portion of the above tube after joining, leakage does not easily occur from the above joint portion. In addition, it is required that the tube for a semiconductor manufacturing apparatus has a low air permeability, that is, excellent gas barrier properties. The present inventors evaluated a tube for a semiconductor manufacturing apparatus formed of a fluorine-containing copolymer described in Patent Document 1, and as a result, found that there is still room for improvement in the above joinability with a joint and gas barrier properties.
[0005] Therefore, the technical problem to be solved by the present invention is to provide a tube for a semiconductor manufacturing apparatus having excellent joinability with a joint and gas barrier properties. Technical Solution for Solving the Technical Problem
[0006] The present inventors conducted an in-depth study on the above technical problem, and as a result, found that for a tube for a semiconductor manufacturing apparatus containing a fluorine-containing polymer, when the above fluorine-containing polymer satisfies a specified requirement A, a tube for a semiconductor manufacturing apparatus having excellent joinability with a joint and gas barrier properties can be obtained, and thus completed the present invention.
[0007] That is, the inventors have found that the above technical problems can be solved by the following constitution. [1] A tube for a semiconductor manufacturing apparatus, which is a tube for a semiconductor manufacturing apparatus containing a fluoropolymer, wherein the fluoropolymer satisfies the following requirement A: (Requirement A) The creep permanent strain of the fluoropolymer is 4.5% or more, The creep rate of the fluoropolymer measured by a tensile creep test is 2.60% or less, The flexural modulus of elasticity of the fluoropolymer is 1100 MPa or less, The crystallinity of the fluoropolymer is 42.0% or more. [2] The tube for a semiconductor manufacturing apparatus according to [1], wherein the fluoropolymer has a unit based on tetrafluoroethylene. [3] The tube for a semiconductor manufacturing apparatus according to [1] or [2], wherein the fluoropolymer further has a unit based on at least one monomer selected from ethylene, propylene, fluoroalkyl vinyl ether, and perfluoro(alkyl vinyl ether). [4] The tube for a semiconductor manufacturing apparatus according to any one of [1] to [3], wherein the fluoropolymer further has a unit based on at least one monomer selected from ethylene and fluoroalkyl vinyl ether. [5] The tube for a semiconductor manufacturing apparatus according to any one of [1] to [4], which is used for semiconductor chemical liquid transportation or gas transportation in a semiconductor manufacturing apparatus. [6] The tube for a semiconductor manufacturing apparatus according to any one of [1] to [4], wherein the crystallinity is 70.0% or less. Advantages of the Invention
[0008] According to the present invention, a tube for a semiconductor manufacturing apparatus having excellent bonding properties and gas barrier properties with a joint can be provided. Detailed Description of the Invention
[0009] The meanings of the terms in this specification are as follows. A numerical range represented by "~" means a range including the numerical values described before and after "~" as the lower limit value and the upper limit value. "Unit" refers to the general term for an atomic group directly formed by polymerization of a monomer and an atomic group obtained by chemically changing a part of the atomic group. The content (mol%) of each unit relative to all units contained in the polymer can be obtained by analyzing the polymer using nuclear magnetic resonance spectroscopy, or can be determined from the feeding amount of the components used in the manufacture of the polymer. In addition, hereinafter, according to the circumstances, the units derived from each monomer are sometimes described by the name of the monomer plus "unit". The "TFE unit" is a unit based on tetrafluoroethylene, and the "E unit" is a unit based on ethylene.
[0010] [Tube for semiconductor manufacturing apparatus] The tube for a semiconductor manufacturing apparatus of the present invention (hereinafter also referred to as "this tube") is a tube for a semiconductor manufacturing apparatus containing a fluoropolymer, wherein the above-mentioned fluoropolymer satisfies the following requirement A. (Requirement A) The creep permanent strain of the fluoropolymer is 4.5% or more. The creep rate of the fluoropolymer measured by a tensile creep test is 2.60% or less. The flexural modulus of elasticity of the fluoropolymer is 1100 MPa or less. The crystallinity of the fluoropolymer is 42.0% or more.
[0011] The reason for obtaining a tube having excellent joint bonding properties and excellent gas barrier properties by containing a fluoropolymer that satisfies Requirement A is not clear, but it is considered as follows. It is speculated that if the creep permanent strain is 4.5% or more, the time from the start of flaring processing for joining the tube by radially expanding the tube until the tube diameter returns to its original state is extended, and the operability of the operation of joining with the joint after flaring processing is improved. It is speculated that if the creep rate is 2.60% or less, creep deformation after the tube is joined to the joint is less likely to occur, and leakage at the joint between the tube and the joint is less likely to occur. It is speculated that if the flexural modulus of elasticity is 1100 MPa or less, the flaring processing of the tube is more convenient, and as a result, joining with the joint is easier. It is speculated that if the crystallinity is 42.0% or more, the structure of the fluoropolymer contained in the tube is in a denser state, and thus the gas barrier property is excellent. Hereinafter, obtaining at least one of the effects of more excellent joint bonding properties and more excellent gas barrier properties is referred to as "the effects of the present invention are more excellent".
[0012] [Fluoropolymer] Hereinafter, the composition of the fluoropolymer will be described, and then the physical properties of the fluoropolymer including Requirement A will be described.
[0013] The fluoropolymer is a polymer containing units having fluorine atoms. From the viewpoint of the heat resistance of the tube, the fluoropolymer preferably has units based on tetrafluoroethylene (hereinafter also referred to as "TFE").
[0014] The fluoropolymer preferably further has units based on monomers (hereinafter also referred to as "other monomers") capable of copolymerizing with TFE units. As specific examples of other monomers, ethylene, propylene, perfluoro(alkyl vinyl ether) (hereinafter also referred to as "PAVE"), fluoroalkyl ethylene (hereinafter also referred to as "FAE"), and hexafluoropropylene can be cited. As specific examples of PAVE, CF2=CFOCF3 (hereinafter also referred to as "PMVE"), CF2=CFOCF2CF3, CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), CF2=CFOCF2CF2CF2CF3, CF2=CFO(CF2)8F can be cited, and PMVE and PPVE are preferred. As specific examples of FAE, CH2=CH(CF2)2F (hereinafter also referred to as "PFEE"), CH2=CH(CF2)3F, CH2=CH(CF2)4F (hereinafter also referred to as "PFBE"), CH2=CF(CF2)3H, CH2=CF(CF2)4H can be cited, and PFEE and PFBE are preferred.
[0015] In addition, as other monomers, vinyl chloride, vinylidene chloride, and vinyl fluoride can also be cited. In addition, as other monomers, monomers having an oxygen-containing polar group can also be cited. As the oxygen-containing polar group, an acid anhydride residue, a hydroxyl group, a carbonyl group-containing group, an acetal group, and an oxacycloalkyl group are preferred, and an acid anhydride residue is more preferred. As the monomer having an acid anhydride residue, a monomer having a cyclic acid anhydride residue is preferred, and itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, and maleic anhydride are more preferred.
[0016] Among them, as the units based on other monomers, the fluoropolymer preferably has units based on at least one monomer selected from ethylene, propylene, fluoroalkyl ethylene, and perfluoro(alkyl vinyl ether), more preferably has units based on at least one monomer selected from ethylene and fluoroalkyl ethylene, and further preferably has units based on at least one monomer selected from ethylene and fluoroalkyl ethylene.
[0017] When the fluoropolymer contains TFE units, from the viewpoint of more excellent heat resistance of the tube, the content of TFE units is preferably 40 to 65 mol%, more preferably 45 to 60 mol%, and further preferably 50 to 60 mol% based on all the units contained in the fluoropolymer.
[0018] When the fluoropolymer has TFE units and other monomer units, the content of TFE units is preferably 40 to 65 mol%, more preferably 45 to 60 mol%, and further preferably 50 to 60 mol% based on the total of TFE units and other monomer units. In addition, the content of other monomer units is preferably 35 to 60 mol%, more preferably 40 to 55 mol%, and still more preferably 40 to 50 mol% relative to the total of the TFE units and other monomer units.
[0019] As one of the preferred forms of the fluoropolymer, a form containing TFE units, ethylene units (hereinafter also referred to as "E units") and FAE units can be cited, and a form composed of TFE units, E units and FAE units is more preferred. At this time, the content of the TFE units is preferably 40 to 64.9 mol%, more preferably 45 to 60 mol%, and still more preferably 50 to 60 mol% relative to the total of the TFE units, E units and FAE units. In addition, the content of the E units is preferably 35.0 to 59.9 mol%, more preferably 35.5 to 54.5 mol%, and still more preferably 36.0 to 49.0 mol% relative to the total of the TFE units, E units and FAE units. In addition, the content of the FAE units is preferably 0.1 to 5.0 mol%, more preferably 0.5 to 4.5 mol%, and still more preferably 1.0 to 4.0 mol% relative to the total of the TFE units, E units and FAE units.
[0020] From the viewpoint of more excellent effects of the present invention, the content of the fluoropolymer is preferably 50 to 100% by mass, more preferably 75 to 100% by mass, and still more preferably 90 to 100% by mass relative to the total mass of the present tube. Two or more kinds of fluoropolymers can be used simultaneously.
[0021] <Physical properties> The physical properties of the fluoropolymer containing Component A will be described in detail below.
[0022] (Creep permanent strain) The creep permanent strain of the fluoropolymer contained in the present tube is 4.5% or more. The creep permanent strain is a value obtained as the ratio (100 × change in the size of the test piece before and after the test / size of the test piece before the test, unit: %) of the change in the size of the test piece before and after the test to the size of the test piece before the test in a compression creep resistance test in which a test piece formed from the fluoropolymer is compressed at a test temperature of 300 °C and a test pressure of 140 kgf / cm 2 for 24 hours and then allowed to stand for 24 hours. The detailed measurement conditions of the creep permanent strain are described in the following Examples column.
[0023] From the perspective of more excellent jointing property with the joint, the creep permanent strain of the fluoropolymer is preferably 4.7% or more, more preferably 5.0% or more. In addition, from the perspective of more excellent liquid leakage resistance after jointing with the joint, the creep permanent strain of the fluoropolymer is preferably 10.0% or less, more preferably 8.5% or less. The creep permanent strain of the fluoropolymer can be adjusted by increasing the molecular weight of the fluoropolymer, changing the crystallinity of the fluoropolymer, etc. By adjusting the molecular weight, the entanglement between molecular chains changes, and the creep permanent strain can be adjusted. In addition, by changing the monomer composition ratio, the crystallinity changes, and the creep permanent strain can be adjusted.
[0024] (Creep rate measured by tensile creep test) The creep rate (hereinafter also referred to as "creep rate") of the fluoropolymer contained in this tube measured by the tensile creep test is 2.60% or less. The creep rate is a value obtained as the ratio (100 × change in chuck spacing before and after the test / chuck spacing before the test, unit: %) of the change in chuck spacing before and after the test with respect to the chuck spacing before the test for a test piece formed from the fluoropolymer according to the standard of ASTM D674 under the conditions of a test temperature of 23°C ± 3°C, a stress of 70 kgf / cm 2 , and a test time of 150 hours. The detailed measurement conditions of the creep rate are described in the following Examples section.
[0025] From the perspective of more excellent jointing property with the joint, the creep rate of the fluoropolymer is preferably 2.10% or less, more preferably 2.00% or less. In addition, the creep rate of the fluoropolymer is preferably 1.00% or more, more preferably 1.20% or more. The creep rate of the fluoropolymer can be adjusted, for example, by making the melt flow rate (hereinafter also referred to as "MFR") of the fluoropolymer fall within the following range (especially 1 - 20 g / 10 minutes).
[0026] (Flexural modulus of elasticity) The flexural modulus of elasticity of the fluoropolymer contained in this tube is preferably 1100 MPa or less. The flexural modulus of elasticity is a value calculated from the stress-strain curve obtained by measuring the stress and strain applied to a test piece formed from the fluoropolymer according to the standard of ASTM D790 in a bending test at 23°C (unit: MPa). The detailed measurement conditions of the flexural modulus of elasticity are described in the following Examples section.
[0027] From the perspective of more excellent adhesion to the joint, the flexural modulus of the fluoropolymer is preferably 1080 MPa or less, more preferably 800 MPa or less. In addition, from the perspective of more excellent pressure resistance, the flexural modulus of the fluoropolymer is preferably 300 MPa or more, more preferably 400 MPa or more. The flexural modulus of the fluoropolymer can be adjusted, for example, by adjusting the crystallinity of the fluoropolymer, adjusting the MFR of the fluoropolymer, etc. Here, reducing the content of units with 3 or more carbon atoms in the fluoropolymer increases the crystallinity, and increasing the content of this unit decreases the crystallinity. For example, by using a fluoropolymer with a crystallinity within the following range, the flexural modulus of the fluoropolymer can be adjusted to the above range. In addition, by making the MFR of the fluoropolymer fall within the following range (especially 1 to 30 g / 10 minutes), the flexural modulus of the fluoropolymer can also be adjusted to the above range.
[0028] (Crystallinity) The crystallinity of the fluoropolymer contained in this tube is 42.0% or more. The crystallinity is obtained by measuring the heat of fusion (J / g) with a differential scanning calorimetry device for a test piece formed from the fluoropolymer, and is the ratio (100 × measured heat of fusion / heat of fusion of a perfect crystal, unit: %) of the above-mentioned heat of fusion to the heat of fusion of a perfect crystal of the measurement object. The detailed measurement conditions of the crystallinity are described in the following example column.
[0029] From the perspective of more excellent gas barrier properties, the crystallinity of the fluoropolymer is preferably 43.0% or more, more preferably 45.0% or more. In addition, from the perspective of more excellent crack resistance, the crystallinity of the fluoropolymer is preferably 70.0% or less, more preferably 60.0% or less. Reducing the content of units with 3 or more carbon atoms in the fluoropolymer increases the crystallinity of the fluoropolymer. It can also be adjusted conversely.
[0030] (Melting point) From the perspective of more excellent heat resistance, the melting point of the fluoropolymer is preferably 200 °C or higher, more preferably 215 °C or higher, and further preferably 230 °C or higher. From the perspective of more excellent formability of the fluoropolymer, the upper limit of the melting point of the fluoropolymer is preferably 290 °C or lower, more preferably 280 °C or lower, and further preferably 270 °C or lower. As a method for making the melting point of the fluoropolymer fall within the above range, methods such as lowering the polymerization temperature during the production of the fluoropolymer and adjusting the content of units having 3 or more carbon atoms in the fluoropolymer can be cited. The melting point of the fluoropolymer is the temperature corresponding to the endothermic peak when the fluoropolymer is heated to 300 °C at a rate of 10 °C / minute in an air atmosphere using a differential scanning calorimeter.
[0031] (Melt flow rate) From the viewpoint of more excellent formability of the fluoropolymer, mechanical strength and abrasion resistance of the molded article, the MFR of the fluoropolymer is preferably 1 to 100 g / 10 minutes, more preferably 1 to 50 g / 10 minutes, still more preferably 1 to 30 g / 10 minutes, and particularly preferably 1 to 20 g / 10 minutes. As a method for making the MFR of the fluoropolymer fall within the above range, a method of adjusting the molecular weight of the fluoropolymer can be cited. The larger the molecular weight of the fluoropolymer, the smaller the MFR. The MFR of the fluoropolymer means the mass of the fluoropolymer flowing out from an orifice having a diameter of 2 mm and a length of 8 mm within 10 minutes measured under the conditions of a temperature of 297 °C and a load of 49 N in accordance with the standard of ASTM D3159.
[0032] <Manufacturing method> The fluoropolymer can be produced by polymerizing the above monomers by using known methods such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. As a manufacturing method of the fluoropolymer, solution polymerization is preferred. In addition to the above monomers, a polymerization initiator, a polymerization medium, a chain transfer agent, etc. can also be used in the production of the fluoropolymer.
[0033] The polymerization initiator is preferably a radical polymerization initiator having a half-life of 10 hours at a temperature of 0 to 100 °C, and more preferably a radical polymerization initiator having the above temperature of 20 to 90 °C. As specific examples of the polymerization initiator, various polymerization initiators exemplified in International Publication No. 2013 / 015202 can be cited. The polymerization initiator can be used alone as one kind, or two or more kinds can be used in combination. The usage amount of the polymerization initiator is preferably 0.01 to 0.9 parts by mass, more preferably 0.05 to 0.5 parts by mass, relative to 100 parts by mass of the usage amount of the monomer.
[0034] As the polymerization medium, perfluorohydrocarbons, hydrofluorocarbons, hydrofluoroethers, etc. can be used. As specific examples of the polymerization medium, various polymerization media exemplified in International Publication No. 2013 / 015202 can be cited. The polymerization medium can be used alone as one kind, or two or more kinds can be used in combination. The usage amount of the polymerization medium is preferably 5 times or more, more preferably 7 times or more, based on the mass ratio relative to the usage amount of the monomer. In addition, it is preferably 20 times or less, more preferably 17 times or less.
[0035] As the chain transfer agent, from the perspective of a large chain transfer coefficient and a small addition amount, alcohols such as methanol, ethanol, 2,2,2-trifluoroethanol, 2,2,3,3-tetrafluoropropanol, 1,1,1,3,3,3-hexafluoroisopropanol, 2,2,3,3,3-pentafluoropropanol, hydrocarbons such as n-pentane, n-hexane, cyclohexane, hydrofluorocarbons such as CF2H2, ketones such as acetone, mercaptans such as methyl mercaptan, esters such as methyl acetate, ethyl acetate, or ethers such as diethyl ether, methyl ethyl ether are preferred. Among them, from the perspective of a higher chain transfer constant and high stability of the end groups of the fluoropolymer, at least one selected from alcohols, hydrocarbons, and hydrofluorocarbons is preferred, more preferably at least one selected from alcohols and hydrocarbons, and further preferably alcohols. Among alcohols, methanol or ethanol is preferred. Among them, from the perspective of reactivity and ease of acquisition, methanol is more preferred. Two or more kinds of chain transfer agents can be used. The usage amount of the chain transfer agent is preferably 0.001 times or more, more preferably 0.005 times or more, based on the mass ratio relative to the usage amount of the monomer. In addition, it is preferably 5 times or less, more preferably 4 times or less.
[0036] The polymerization temperature is preferably 15 to 100 °C, more preferably 20 to 90 °C, and further preferably 25 to 80 °C. If the polymerization temperature is above the above lower limit value, the polymerizability is excellent. If the polymerization temperature is below the above upper limit value, the melting point of the fluoropolymer can be increased. The polymerization pressure is preferably 0.5 to 3.0 MPa, more preferably 0.9 to 2.5 MPa. The polymerization time is preferably 1 to 12 hours.
[0037] 〔Other components〕 This tube may further contain components other than the above-mentioned fluoropolymer (hereinafter also referred to as "other components") within the range where the effects of the present invention can be fully exerted. As specific examples of other components, heat stabilizers, antioxidants, polymers other than fluoropolymers, colorants, ultraviolet absorbers, fillers, crosslinking agents, and crosslinking aids can be cited. When this tube contains other components, the content of the other components is preferably 99% by mass or less, more preferably 50% by mass or less, and further preferably 10% by mass or less, based on the total mass of this tube. Two or more kinds of other components can be used in combination.
[0038] 〔Shape of the tube〕 This tube is a tubular member with both ends open. From the perspective of better exerting the effect of pressure resistance and flexibility, the thickness of this tube is preferably 4 mm or less, more preferably 3 mm or less, and further preferably 2 mm or less. In addition, from the perspective of more excellent pressure resistance and flexibility, the thickness of this tube is preferably 0.1 mm or more, more preferably 0.5 mm or more. In addition, the thickness of this tube is a value obtained by dividing the difference between the outer diameter and the inner diameter of this tube by 2. In addition, pressure resistance and flexibility refer to the property of not undergoing large flexure and being difficult to be bent under pressure when assembled into a semiconductor manufacturing apparatus (hereinafter also referred to as "pressure resistance and flexibility").
[0039] The outer diameter of this tube is preferably 1 to 55 mm, more preferably 1 to 40 mm, and further preferably 1 to 35 mm. The inner diameter of this tube is shorter than the outer diameter, preferably 0.5 to 50 mm, more preferably 0.5 to 40 mm, and further preferably 0.5 to 35 mm.
[0040] Examples of the shape of the open end of the tube and the shape of the cross-section of the tube perpendicular to the long side direction include, for example, a circle, an ellipse, and a polygon. A circle or an ellipse is preferred, and a circle is more preferred.
[0041] 〔Method for manufacturing the tube〕 This tube can be manufactured by melt-molding a fluoropolymer in the form of powder, granules, particles, or other forms. Examples of the melt-molding method include known methods such as extrusion molding, injection molding, blow molding, compression molding, and rotational molding. The melt-molding temperature is a temperature higher than the melting temperature of the fluoropolymer, and preferably a temperature 50 to 200 °C (more preferably 50 to 150 °C) lower than the thermal decomposition temperature of the fluoropolymer.
[0042] This tube can also be manufactured by melt-molding a composition containing a fluoropolymer and the above-mentioned other components. The content of the fluoropolymer in the above-mentioned composition is preferably 50% by mass or more and less than 100% by mass, more preferably 70% by mass or more and less than 100% by mass, and particularly preferably 90% by mass or more and less than 100% by mass with respect to the total mass of the composition. The content of the other components in the above-mentioned composition is preferably higher than 0% by mass and 50% by mass or less, more preferably higher than 0% by mass and 30% by mass or less, and further preferably higher than 0% by mass and 10% by mass or less with respect to the total mass of the composition. The composition can be manufactured by a method of melt-kneading a fluoropolymer and the above-mentioned other components used as needed by a known method.
[0043] As a method for manufacturing this tube, from the perspective of being able to manufacture a tube with a constant cross-sectional shape, extrusion molding is preferably used. As an extruder for extrusion molding, an extrusion molding machine equipped with a hopper, a screw, a barrel, a connector (the connecting part between the screw and the die head), and a die head can be cited. The extruder can be a single-screw extruder or a twin-screw extruder. It is also possible to remove the volatile components generated by the fluoropolymer by providing exhaust holes on the barrel and opening the exhaust holes.
[0044] In the extrusion molding using the above extruder, the barrel temperature is preferably 150 to 400 °C, more preferably 180 to 390 °C. In addition, the die head temperature is preferably 200 to 380 °C, more preferably 210 to 370 °C.
[0045] 〔Use〕 This tube is a tube for semiconductor manufacturing equipment. This tube has excellent bondability, is easy to bond with connectors, and is not prone to leakage after bonding. Therefore, it is particularly suitable for use as a tube for transporting semiconductor chemical liquids or gases inside semiconductor manufacturing equipment used in semiconductor manufacturing equipment. The above semiconductor chemical liquid is a chemical liquid used in the manufacturing process of semiconductors. More specifically, etching liquids, developing liquids, rinsing liquids, and cleaning liquids can be cited. The above gas is a gas supplied to semiconductor manufacturing equipment for use in the manufacturing process of semiconductors. More specifically, raw material gases for semiconductor film-forming materials, process gases used in various processes such as etching, developing, rinsing, and cleaning, and inert gases can be cited.
[0046] In addition, this tube is also suitable for use as a tube for transporting liquids or gases in fields such as pharmaceutical manufacturing, medical devices, analytical devices, and food manufacturing, which require reduction of contamination and fouling from machines. Examples
[0047] Hereinafter, the present invention will be described in detail with examples. Example 1 and Example 2 are examples, and Example 3 to Example 5 are comparative examples. However, the present invention is not limited to these examples.
[0048] <Determination of the composition of the fluoropolymer> The content (mol%) of each unit in the fluoropolymer is calculated by 19 F - nuclear magnetic resonance (NMR) measurement. Among them, the content of ethylene (E) units in the fluoropolymer is calculated by 1 H and 13 C - NMR measurement.
[0049] <Determination of the melting point> The melting point (°C) of the fluoropolymer was determined from the endothermic peak when heating the fluoropolymer to 300°C at a rate of 10°C / min in an air atmosphere using a differential scanning calorimeter (trade name “DSC7020”, manufactured by Hitachi High-Technologies Corporation (Hitachi High-Tech Science Corporation)).
[0050] <Measurement of MFR> Using a melt indexer (manufactured by Techno Seven Co., Ltd.), the mass (g) of the fluoropolymer flowing out of an orifice with a diameter of 2 mm and a length of 8 mm within 10 minutes was measured under the conditions of a temperature of 297°C and a load of 49 N in accordance with the standard of ASTM D3159, which is the MFR (g / 10 min).
[0051] [Example 1] <Synthesis of Fluoropolymer 1> After degassing the inside of a 215-liter stainless-steel autoclave equipped with a stirrer, 208.6 kg of CF3(CF2)5H, 1.9 kg of methanol, and 0.95 kg of perfluorobutylethylene (PFBE) were charged. The mixture was heated to 66°C while stirring, and a mixed gas of tetrafluoroethylene (TFE) / ethylene (E) = 83 / 17 (mol%) was introduced into the autoclave until the pressure inside the autoclave reached 1.5 MPaG. Next, a CF3(CF2)5H solution (concentration 1 mass%) of 524 g of tert-butyl peroxyneodecanoate was injected into the autoclave to start the polymerization. During the polymerization, a mixed gas of TFE / E = 54 / 46 (mol%) and PFBE in an amount equivalent to 1.4 mol% of the mixed gas were continuously added to the autoclave to keep the pressure inside the autoclave at 1.5 MPaG. Ten hours after the start of the polymerization, when the addition amount of the mixed gas reached 13.5 kg, the inside of the autoclave was cooled to 23°C to end the polymerization. Then, a part of the residual mixed gas was removed to obtain Slurry 1. 120 kg of the obtained Slurry 1 was stored in a storage tank, and the obtained Slurry 1 was put into a 220-liter granulation tank containing 77 kg of water. Next, the mixture was heated to 105°C while stirring to distill off the solvent, thereby performing granulation. The powdery granulated product was recovered to obtain Fluoropolymer 1.
[0052] The composition of the obtained Fluoropolymer 1 was 53.4 / 44.9 / 1.5 in terms of the molar ratio of TFE units / E units / PFBE units. In addition, the melting point of Fluoropolymer 1 was 259°C, and the MFR of Fluoropolymer 1 was 6.7 g / 10 min.
[0053] <Manufacture of Granule 1> The obtained fluoropolymer 1 was melt-kneaded using a single-screw extruder with a diameter of 30 mm, and the resulting strand-shaped formed article was cut using a granulator to obtain granules 1 of fluoropolymer 1. When melt-kneading fluoropolymer 1, the barrel temperature was set to 260 - 320 °C, and the die head temperature was set to 320 °C.
[0054] <Manufacture of Tube 1> A tube manufacturing apparatus was prepared, which included a single-screw extruder with a diameter of 30 mm (manufactured by Tanabe Plastic Machinery Co., Ltd.) for preparing a tube from the granules of the fluoropolymer, a pulling machine for pulling the tube, and a winding machine for winding the tube. The obtained granules 1 of fluoropolymer 1 were supplied to the single-screw extruder of the above tube manufacturing apparatus for melt-kneading, and the melt-kneaded material was extruded from the single-screw extruder into a tubular shape, thereby manufacturing tube 1 with an inner diameter of 11.1 mm and an outer diameter of 12.7 mm in cross-section. The compression ratio of the screw in the single-screw extruder was 3, and L (effective length of the screw) / D (diameter of the screw) was 24. In the single-screw extruder, the barrel temperature was set to 250 - 290 °C, and the die head temperature was set to 290 °C. In addition, the pulling speed of tube 1 was adjusted to 1 m / minute.
[0055] [Example 2] <Synthesis of Fluoropolymer 2> After degassing a polymerization tank with a stirrer having an internal volume of 260 liters, 54.6 kg of deionized water, 173.3 kg of 1-Hydrotridecafluorohexane, and 19.3 kg of methanol were introduced into the polymerization tank. Then, 31.4 kg of tetrafluoroethylene (TFE), 0.86 kg of ethylene (E), and 2.12 kg of PFBE were introduced. Subsequently, the mixture in the polymerization tank was heated to 66 °C (polymerization temperature) while stirring, and a 2.0 mass% 1-Hydrotridecafluorohexane solution of 1.54 L of tert-Butyl peroxyneopentanoate was introduced into the polymerization tank to start the polymerization. During the polymerization process, a monomer mixed gas with a composition of TFE / E = 60 / 40 (molar ratio) was continuously introduced, and PFBE equivalent to 3.3 mol% of the TFE / E monomer mixed gas was continuously introduced to keep the pressure in the polymerization tank constant. The pressure in the polymerization tank during the polymerization process was maintained at 1.5 MPa (gauge pressure). 3.5 hours after the start of polymerization, when 22 kg of the monomer mixed gas had been introduced, the temperature in the polymerization tank was cooled to room temperature (23 °C) to end the polymerization. Subsequently, the inside of the polymerization tank was cleaned, and the pressure was reduced to atmospheric pressure (1 atm) to obtain the slurry 2 in the polymerization tank. The obtained slurry 2 was suction-filtered using a glass filter, and the filtered product was dried at 120 °C for 15 hours to obtain fluoropolymer 2.
[0056] The composition of the obtained fluoropolymer 2 is 57.1 / 39.5 / 3.4 in terms of the molar ratio of TFE units / E units / PFBE units. In addition, the melting point of fluoropolymer 2 is 231 °C, and the MFR of fluoropolymer 2 is 13 g / 10 min.
[0057] <Manufacture of Particle 2> Except for using the synthesized fluoropolymer 2, setting the barrel temperature in the single-screw extruder to 220 - 280 °C, and setting the die head temperature to 280 °C, according to the method described in <Manufacture of Particle 1> of Example 1, Particle 2 of fluoropolymer 2 was manufactured.
[0058] <Manufacture of Tube 2> Except for using the manufactured Particle 2, setting the barrel temperature in the single-screw extruder to 300 - 320 °C, and setting the die head temperature to 320 °C, according to the method described in <Manufacture of Tube 1> of Example 1, a tube 2 with an inner diameter of 11.1 mm and an outer diameter of 12.7 mm for the cross-section was manufactured.
[0059] [Example 3] As fluoropolymer 3, Particle 3 composed of PFA was prepared. The composition of fluoropolymer 3 is 98.5 / 1.5 in terms of the molar ratio of TFE units / perfluoropropyl vinyl ether units. In addition, the melting point of fluoropolymer 3 is 307 °C, and the MFR of fluoropolymer 3 is 2 g / 10 min.
[0060] <Manufacture of Tube 3> Except for using the prepared Particle 3, setting the barrel temperature in the single-screw extruder to 340 - 380 °C, setting the die head temperature to 380 °C, and adjusting the pulling speed of the tube to 0.6 m / min, according to the method described in <Manufacture of Tube 1> of Example 1, a tube 3 with an inner diameter of 11.1 mm and an outer diameter of 12.7 mm for the cross-section was manufactured.
[0061] [Example 4] <Synthesis of Fluoropolymer 4> After degassing a 260-liter stainless-steel polymerization tank equipped with a stirrer and a jacket, 165 kg of CF3CH2OCF2CF2H and 0.64 kg of PFBE(CH2=CH(CF2)4F) were charged into the polymerization tank. Then, while stirring the mixture, 70 kg of hexafluoropropylene (HFP), 23.6 kg of TFE, and 0.58 kg of E were charged, and then warm water was passed through the jacket to raise the temperature in the polymerization tank to 66 °C. At this time, the pressure in the polymerization tank is 1.47 MPa (gauge pressure). After the temperature in the polymerization tank stabilizes, 1.48 L of a 5% by mass solution of tert-butyl peroxyneopentanoate in CF3CH2OCF2CF2H is introduced into the polymerization tank, and polymerization is started. During the polymerization process, a mixed gas having a composition of TFE / E = 54 / 46 (molar ratio) is added to the polymerization tank so that the pressure in the polymerization tank is kept constant at 1.47 MPa (gauge pressure). Further, for every 1 kg of the TFE / E mixed gas consumed during the polymerization process, 0.4 L of a CF3CH2OCF2CF2H solution containing 7.1% by mass of PFBE and 1.3% by mass of itaconic anhydride is added to the polymerization tank. 370 minutes after the start of polymerization, when 14 kg of the mixed gas has been added, the inside of the polymerization tank is cooled to 23°C, and polymerization is terminated. Then, a part of the residual mixed gas is removed from the polymerization tank, and the pressure in the polymerization tank is reduced to atmospheric pressure to obtain Slurry 4. The obtained Slurry 4 is transferred to a container having an internal volume of 300 L, water having the same volume as Slurry 4 is added, and the mixture is heated (20 to 73°C) to separate the polymerization solvent, the remaining unreacted monomers, and the product. The obtained product is dried in an oven at 120°C to obtain a white powdery fluoropolymer 4.
[0062] The composition of the fluoropolymer 4 is 47.5 / 43.4 / 8.3 / 0.6 / 0.3 in terms of the molar ratio of TFE unit / E unit / HFP unit / PFBE unit / itaconic anhydride unit. In addition, the melting point of the fluoropolymer 4 is 191°C, and the MFR of the fluoropolymer 4 is 2 g / 10 minutes.
[0063] <Production of Granules 4> Granules 4 of the fluoropolymer 4 are produced in accordance with the method described in <Production of Granules 1> of Example 1, except that the synthesized fluoropolymer 4 is used and the barrel temperature in the single-screw extruder is set to 180 to 240°C and the die temperature is set to 240°C.
[0064] <Production of Tube 4> A tube 4 having an inner diameter of 11.1 mm and an outer diameter of 12.7 mm in cross section is produced in accordance with the method described in <Production of Tube 1> of Example 1, except that the produced granules 4 are used and the barrel temperature in the single-screw extruder is set to 200 to 240°C and the die temperature is set to 240°C.
[0065] [Example 5] As the fluoropolymer 5, granules 5 containing polyvinylidene fluoride (PVdF) are prepared. The melting point of the fluoropolymer 5 is 173°C, and the MFR of the fluoropolymer 5 is 20 g / 10 minutes.
[0066] <Manufacture of Tube 5> Except for using the prepared particles 5, setting the barrel temperature in the single-screw extruder to 190 - 230°C, setting the die temperature to 230°C, and adjusting the pulling speed of the tube to 0.6 m / min, a tube 5 with an inner diameter of 11.1 mm and an outer diameter of 12.7 mm in cross-section was manufactured according to the method described in <Manufacture of Tube 1> of Example 1.
[0067] [Measurement of Physical Properties] For the fluoropolymer of each example, the following physical properties were measured.
[0068] <Creep Permanent Strain> The particles of each example were melt-molded at a temperature (230 - 360°C) taking into account the melting point of the fluoropolymer contained in the particles to prepare a pressed sheet 2 cm thick. By machining, 3 samples with a height of 1.5 cm and a bottom area of 1 cm 2 were prepared from the obtained pressed sheet. According to the standard of ASTM D621, the creep permanent strain of the obtained samples was measured using a compression testing machine. More specifically, after applying a load of 140 kgf / cm 2 to the sample at a temperature of 23°C for 24 hours, the pressure was released, and the sample was left standing at a temperature of 23°C for 24 hours. The dimensions (height) of the sample before applying the load and the dimensions (height) of the sample after standing for 24 hours were measured, and the deformation rate (unit: %) was calculated based on the following formula from the sample dimensions before and after the load test. The arithmetic mean of the deformation rates of the 3 samples was taken, and this value was the creep permanent strain. Deformation rate = 100×((dimension before load test) - (dimension after load test)) / (dimension before load test)
[0069] <Creep Rate> The particles of each example were melt-molded at a temperature (230 - 360°C) taking into account the melting point of the fluoropolymer contained in the particles to prepare a pressed sheet with a thickness of 2 mm and dimensions of 130 mm × 130 mm. The obtained pressed sheet was blanked into a dumbbell shape of Type 4 according to ASTM D638 (2 mm thick) to prepare 3 samples. According to the standard of ASTM D674, the creep rate of the obtained samples was measured using a tensile testing machine. More specifically, after placing the sample on the tensile testing machine, a tensile creep test was carried out at a stress of 70 kgf / cm 2 for 150 hours in an environment at a temperature of 23°C ± 3°C. The deformation rate (unit: %) was calculated based on the following formula from the chuck spacing before and after the tensile creep test. The arithmetic mean of the deformation rates of the 3 samples was taken, and this value was the creep rate. In addition, the chuck distance when the tensile creep test time is 100 hours is defined as the chuck distance after the test in the following formula. Deformation rate (%) = 100 × {(chuck distance after test) - (chuck distance before test)} / chuck distance before test
[0070] <Flexural modulus> The pellets of each example were melt-molded at a temperature (230 to 360° C.) taking into account the melting point of the fluoropolymer contained in the pellets, thereby preparing a pressed sheet of 127 mm×10 mm×3 mm thick using an injection molding machine (manufactured by FANUC). The flexural modulus (MPa) of the test specimens was measured using a large-scale tensile testing machine (RTF-1350) in accordance with ASTM D790 at a temperature of 23°C, a support distance of 40 mm, and a speed of 1 mm / min. The flexural modulus was calculated from the slope of the stress-strain curve within the stress range of 0.3 to 1.2 kgf. The flexural modulus of the five test specimens was calculated as the arithmetic average.
[0071] <Crystallinity> For each pellet, the heat of fusion (J / g) was measured three times using a differential scanning calorimeter (DSC7000X, manufactured by Hitachi High-Technologies Corporation) at a heating rate of 10°C / min and a measurement range of 23°C to 400°C. The obtained heats of fusion were arithmetic averaged, and the ratio of the heat of fusion (J / g) of the measured pellet to the heat of complete crystalline fusion (J / g) of the measured pellet was calculated (100 × measured heat of fusion / heat of complete crystalline fusion, unit: %). In addition, in this specification, the complete crystalline melting heat (J / g) of fluoropolymer 1 is set to "113.4 (J / g)", the complete crystalline melting heat (J / g) of fluoropolymer 2 is set to "113.4 (J / g)", the complete crystalline melting heat (J / g) of fluoropolymer 3 is set to "38.8 (J / g)", the complete crystalline melting heat (J / g) of fluoropolymer 4 is set to "113.4 (J / g)", and the complete crystalline melting heat (J / g) of fluoropolymer 5 is set to "104.7 (J / g)".
[0072] [evaluate] The following evaluation tests were performed on the tubes produced in each example.
[0073] <Adhesion to Joint> After cutting the tube with a tube cutting machine so that the cut surfaces at both ends are parallel, place the tube on the tube seat of a lever type press fitting jig. Install an accessory for flaring on the press fitting jig and perform a flaring process to expand the tube radially in a cold flaring manner. After the flaring process, remove the clamp of the press fitting jig, take out the tube, and join the taken-out tube to the joint. Then, tighten the joint portion of the tube and the joint with a nut. Next, join the tube joined with the joint to an air compressor with a commercially available rubber tube. Reinforce with vinyl tape and fasteners so that there is no air leakage at the joint surface between the rubber tube and the resin tube. Immerse the tube joined with the joint in a water tank and supply air at a pressure of 1 MPa with an air compressor, and observe for 10 minutes whether there is air leakage from the joint surface between the joint and the tube. Based on the following criteria, evaluate the joint property between the tube and the joint according to the difficulty of the flaring process of the tube, the time taken for joining the tube and the joint, and the result of the liquid leakage test at the joint portion between the tube and the joint. In addition, prepare 5 tubes for each example for evaluation.
[0074] (Joint Property Evaluation Criteria) 4... The average time of the sum of the time taken for the flaring process and the time taken for joining to the joint is 10 seconds or less, and it is easy to connect. In addition, the number of tubes with liquid leakage is 0. 3... The average time of the sum of the time taken for the flaring process and the time taken for joining to the joint is more than 10 seconds and 20 seconds or less, and it is easy to connect. In addition, the number of tubes with liquid leakage is 0 - 1. 2... The average time of the sum of the time taken for the flaring process and the time taken for joining to the joint is more than 20 seconds, but it can be connected. In addition, the number of tubes with liquid leakage is 0 - 2. 1... It is impossible to join to the joint, or heating is required for joining. In addition, the number of tubes with liquid leakage is 3 or more.
[0075] (Gas Barrier Property) Melt and mold the particles of each example at a temperature (230 - 360 °C) considering the melting point of the fluoropolymer contained in the particles to prepare 3 pressed sheets with a size of 130 mm × 130 mm × 0.1 mm thick. For the obtained pressed sheets, measure the gas permeability of nitrogen and oxygen (10 -16 mol·m / (s·m 2 ·Pa)) by the differential pressure method under the conditions of 23 °C and 1 atm according to the standard of JIS K7126, take the arithmetic mean of the gas permeabilities of the 3 samples, and evaluate the gas barrier property based on this value according to the following criteria. In addition, although the gas barrier property of the pressed sheet is evaluated, the pressed sheet and the tube are both molded bodies, so the evaluation result of the gas barrier property of the pressed sheet tends to be the same as the result when evaluated using the tube.
[0076] (Gas barrier property evaluation criteria) A: The gas permeabilities of oxygen and nitrogen are below 3.5. B: The gas permeabilities of oxygen and nitrogen are greater than 3.5 and below 5.0. C: The gas permeabilities of oxygen and nitrogen are greater than 5.0.
[0077] [Table 1]
[0078] As shown in Table 1, it was confirmed that the tubes and joints made of the fluoropolymer satisfying Requirement A using the formed body had excellent joint properties and excellent gas barrier properties (Examples 1 and 2).
[0079] In addition, the entire contents of the specification, claims, and abstract of Japanese Patent Application No. 2022-212129 filed on December 28, 2022 are hereby incorporated by reference as the disclosure of the present invention.
Claims
1. A tube for a semiconductor manufacturing apparatus, which is a tube for a semiconductor manufacturing apparatus containing a fluoropolymer, wherein, The fluoropolymer satisfies the following requirement A: Requirement A The creep permanent strain of the fluoropolymer is 4.5% or more, The creep rate of the fluoropolymer measured by a tensile creep test is 2.60% or less, The flexural modulus of elasticity of the fluoropolymer is 1100 MPa or less, The crystallinity of the fluoropolymer is 42.0% or more.
2. The tube for a semiconductor manufacturing apparatus according to claim 1, wherein, The fluoropolymer has units based on tetrafluoroethylene.
3. The tube for a semiconductor manufacturing apparatus according to claim 2, wherein, The fluoropolymer further has units based on at least one monomer selected from ethylene, propylene, fluoroalkyl ethylene, and perfluoro(alkyl vinyl ether).
4. The tube for a semiconductor manufacturing apparatus according to claim 2, wherein, The fluoropolymer further has units based on at least one monomer selected from ethylene and fluoroalkyl ethylene.
5. The tube for a semiconductor manufacturing apparatus according to any one of claims 1 to 4, which is used for semiconductor chemical liquid transportation or gas transportation within a semiconductor manufacturing apparatus.
6. The tube for a semiconductor manufacturing apparatus according to any one of claims 1 to 4, wherein, The crystallinity is 70.0% or less.
Citation Information
Patent Citations
Fluorine-containing copolymer composition
WO2013015202A1
Fluororesin molded body
WO2019003265A1